Acute Disseminated Encephalomyelitis in a 2-Year-Old Patient Following COVID-19 - Robinson, Amy; Chapman, Louise; Watts, Wendy (Journal of Pediatric Neurology, 2021)
This report presents the case of acute disseminated encephalomyelitis in a 2-year-old patient following a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test. She presented with ataxic gait, truncal ataxia, and reduced coordination following 10 days of intermittent fever and lethargy. She did not have any respiratory symptoms. Magnetic resonance imaging of the brain and spine showed widespread T2 high signal within the gray and white matters and within the spinal cord. She was treated with intravenous methylprednisolone followed by tapering oral prednisolone; this led to resolution of her neurological symptoms. This case highlights that neurological complications can occur secondary to SARS-CoV-2 infection.
Keywords: coronavirus; acute disseminated encephalomyelitis; neurology; pediatrics